The Resistance of Lactic Acid Bacteria Isolated From the Faeces of Broiler chicken towards the Conditions of the Broiler Digestive Tract - A. Mujnisa; L. A. Rotib; N. Djide; A. Natsir (Jurnal Ilmu dan Teknologi Peternakan, 2013)
This research was conducted to determine the resistance degree of lactic acid bacteria (LAB) isolated from the faeces of broilers towards various intestinal conditions, in order to select a lactic acid bacteria to be used as prospective probiotic.  Ten types of LAB bacteria  (M1, M2, M3, M4, M5, M7, M8, M23 ,M26, and M28) isolated from the faeces of broiler chicken were subjected to pH2, pH3, and pH4; to 3% bile salt and to the temperatures of 30oC, 37oC and 41oC. The results of the research showed that all LAB isolates experienced the highest colony reductions at pH2, which was  around 3.2-5.5 log units/ml. The reduction of colony numbers at pH3  was approximately 1.8-3.1 log unit/ml, and the reduction at pH4 was around 1.0 – 2.5 log unit/ml. All the LAB isolates experienced a decrease of 0.5 log unit/ml to 1.6 log unit/ml  in colony numbers after bile salt exposure. The reduction of colony numbers  of ten LAB isolates at the temperatures of 30oC, 37oC and 41oC was 0.6 - 1.4 log unit/ml ; 0.1 – 0.5 log unit/ml and 0.7 – 1.4 log unit/ml, respectively. None of the ten  isolates posses all of the expected characteristic, however based on its more superior ability to block the pathogenic micro-organism as well as its ability to survive in simulated gastro intestinal tract conditions, M1 was selected as prospective probiotic.